Chief executive compensation - part and parcel of the agency problem: empirical evidence from Pakistan / Mohsin Ali Patel, Aamir Firoz Shamsi and Muhammad Asim. - Patel, Mohsin Ali; Shamsi, Aamir Firoz; Asim, Muhammad (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2018)
As per the agency theory, there is a conflict of interest between shareholders and managers. Shareholders are the principal and managers are the agents of a company. Both these parties have different objectives. So, these top executives who are hired to safeguard the interests of shareholders, after a period might start working for their own personal interests like, increase in the amount of their compensation and benefits, and, on the contrary, shareholders might wish to decrease operating expenses, salaries and aim for higher profits, or dividends. The objective of this study is to study the agency theory with reference to an insight to compensation for chief executives in Pakistan. It aims to find the effect of shareholder dividends, financial performance and firm size on executive compensation. The results show that market capitalization and return on assets are the major factors effecting executive compensation. However, interestingly, shareholder dividends do not show to have any effect on compensation.